Fodor's 2009 Caribbean ports of call. - Fodor's Travel Publications, Inc. (New York : Fodor's Travel Pub., 2009)
Provides a travel guide to the ports of the Carribbean; and includes lodging, dining, beaches, shore excursions, and recreational activities for readers who plan on taking a cruise.
Cover title: Caribbean ports of call 2009.
Includes index.
Young Adult
Keywords: Caribbean Area -- Guidebooks; Caribbean Region -- Guidebooks